Catalogue of herpetological types in the collection of the Bombay Natural History Society - Das, I.; Chaturvedi, Naresh (Centre for Herpetology, Madras Crocodile Bank Trust, 1998)
The herpetological types of the Bombay Natural History Society, Bombay (now Mumbai), India, are listed, current to 11 October, 1998. The collection includes historical specimens collected by Major Frank Wall, from India, Myanmar (formerly Burma) and Iran, as well as those described more recently. The annotated list includes original citations, registration numbers, nature of type and present status of every taxa, with additional remarks where necessary. In all, 24 primary and secondary types are present, including 21 name-bearing taxa (including three Anura, three Sauria and 13 Serpentes).